2013
DOI: 10.1093/abbs/gmt031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies on 3D structures of the hydrophobic region PrP(109-136)

Abstract: Prion diseases, traditionally referred to as transmissible spongiform encephalopathies, are invariably fatal and highly infectious neurodegenerative diseases that affect a wide variety of mammalian species, manifesting as scrapie in sheep, bovine spongiform encephalopathy (or 'mad-cow' disease) in cattle, and Creutzfeldt-Jakob disease, Gerstmann-Strussler-Scheinker syndrome, fatal familial insomnia (FFI), and Kulu in humans, etc. These neurodegenerative diseases are caused by the conversion from a soluble norm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…Currently, there is no structural information about prion AGAAAAGA amyloid fibrils because of unstable, noncrystalline and insoluble nature of this region, though numerous laboratory experimental results have confirmed this region owning an amyloid fibril forming property (initially described in 1992 by Stanley B. Prusiner's group). We also did accurate computer calculations on this region and confirmed the amyloid fibril property in this palindrome region [67,73].…”
Section: The Hybrid Idea and Some Hybrid Optimization Methodssupporting
confidence: 56%
“…Currently, there is no structural information about prion AGAAAAGA amyloid fibrils because of unstable, noncrystalline and insoluble nature of this region, though numerous laboratory experimental results have confirmed this region owning an amyloid fibril forming property (initially described in 1992 by Stanley B. Prusiner's group). We also did accurate computer calculations on this region and confirmed the amyloid fibril property in this palindrome region [67,73].…”
Section: The Hybrid Idea and Some Hybrid Optimization Methodssupporting
confidence: 56%
“…In the present study, the variant at codon 127 in particular was highly polymorphic. Amino acids at codon 126 and 127 are localized in the highly conserved glycine rich motif GAVVG 126 G 127 LGGYMLG.This residue was reported to antagonize prion disease development by blocking amyloidal fibril formation [2]. A recent work by Vitale et al,2019 reported polymorphism at this position and implicated its importance in the normal cellular function of prion protein [21].The sequence variation in palindrome residue (PrP 113-120 ) and glycine repeat regions (PrP 124-128 ) synergistically may affect cellular prion protein conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The MD methods employed are the same as the previous studies (Zhang & Zhang, 2013Zhang, 2010Zhang, & 2011c. Briefly, all simulations used the ff03 force field of the AMBER 11 package (Case et al, 2010).…”
Section: Methodsmentioning
confidence: 99%